T helper type 2 inflammatory disease in the absence of interleukin 4 and transcription factor STAT6 - Alexander L. Dent; Jane Hu‐Li; William E. Paul; Louis M. Staudt (1998)
An important signaling pathway for the differentiation of T helper type 2 (TH2) cells from uncommitted CD4 T cell precursors is activation of the STAT6 transcription factor by interleukin 4 (IL-4). The protooncogene BCL-6 is also involved in TH2 differentiation, as BCL-6 −/− mice develop an inflammation of the heart and lungs associated with an overproduction of TH2 cells. Surprisingly, IL-4 −/− BCL-6 −/− and STAT6 −/− BCL-6 −/− double-mutant mice developed the same TH2-type inflammation of the heart and lungs as is characteristic of BCL-6 −/− mice. Furthermore, a TH2 cytokine response developed in STAT6 −/− BCL-6 −/− and IL-4 −/− BCL-6 −/− mice after immunization with a conventional antigen in adjuvant. In contrast to these in vivo findings, STAT6 was required for the in vitro differentiation of BCL-6 −/− T cells into TH2 cells. BCL-6, a transcriptional repressor that can bind to the same DNA binding motifs as STAT transcription factors, seems to regulate TH2 responses in vivo by a pathway independent of IL-4 and STAT6.